SUSTAINABILITY CONCEPT: CULTURAL BASED METHOD IN BUILDING GURUSINA SAO IN FLORES-NUSA TENGGARA TIMUR - Khotijah Lahji; Agustin Rebecca Lakawa (International Journal on Livable Space, 2017)
Traditional house (Sao) in Gurusina Flores is a building designed based on local wisdom by considering the concept of cultural sustainability, the balance of ecosystem (human and nature), and the concept of green building. One of the aspects that becomes the basic concept of environmentally friendly architecture and affects sustainability of a building is the concept of building a traditional house. This study aims to find the concept of sustainability applied by the Gurusina community as they build their traditional houses through cultural aspects that are believed to be inherited through the concept of inner space hierarchy, the space form, and the construction system. The research method is conducted through field observation, measurement, and interview. The results of this study reveal that traditional community of Gurusina has implemented the concept of sustainability in the form of cultural sustainability which has been applied in the phases of building Sao from planning, development and design, as well as construction. Nevertheless, sustainability aspects of the balance in ecosystem, the health and comfort and the waste reduction should also be taken into account in order to achieve the concept of total sustainability.Keywords: Sustainability, Vernacular, Traditional house, Gurusina Sao